Bangladesh’s Foreign Policy : A Comparative Study on India, China, and Pakistan During and Beyond the Sheikh Hasina Era - Sureshan, Atul (2025)
Bangladesh is a relatively small South Asian state located between two major regional powers, India and China. Formerly known as East Pakistan, it achieved independence in 1971 after a violent and protracted conflict characterized by widespread atrocities perpetrated by the Pakistani Army. This thesis examines the evolution of Bangladesh’s foreign policy toward India, China, and Pakistan during and in the aftermath of the tenure of Sheikh Hasina, who served as Prime Minister from 2009 onward. It seeks to identify the principal factors shaping the country’s shifting strategic orientation. The study employs Neoclassical Realism as its theoretical framework, given the emphasis on the role of Sheikh Hasina’s leadership and the domestic determinants influencing Bangladesh’s foreign policy behavior toward the states included in the case study. By tracing the trajectory of Bangladesh’s foreign policy toward India, China, and Pakistan under Sheikh Hasina and following the collapse of her government, the research finds that Bangladesh pursued a distinctly pro-India orientation during her time in office. However, after her removal from power, this orientation shifted toward a more antagonistic stance vis-à-vis India. Conversely, Bangladesh’s policy toward Pakistan remained markedly hostile under Sheikh Hasina, while the interim government that succeeded her initiated efforts to restore and improve bilateral relations. Notably, China has consistently functioned as an “all-weather friend” of Bangladesh, with both states maintaining a strong and stable bilateral relationship throughout and beyond the Sheikh Hasina era.